Pediatric autoimmune retinopathy and optic neuropathy: a case report and a review of the literature - Varma, Hersh; Zhang, Kevin X.; Shah, Veeral S. (Frontiers in Ophthalmology, 2023)
Purpose The purpose of the study was to present a rare case of pediatric bilateral optic neuropathy and retinopathy, which was consistent with a diagnosis of autoimmune retinopathy. We also reviewed the most current literature and phenotypes associated with reported pediatric cases of autoimmune retinopathy. Design The design of the study was a case report, with a retrospective case series literature review. Subjects This study incorporated data from six subjects, with one presenting as an original case report and five being identified from the English-language literature published to date. Materials and methods The materials and methods involved a descriptive analysis of fundus findings, electrophysiologic testing, serum autoantibody testing, optical coherence tomography (OCT), brain MRI scanning, and fluorescein angiography, which were performed where available. Main outcome measures The study evaluated the clinical presentation and treatment outcomes of all subjects and followed their visual function over time. Results All six subjects had retinal abnormalities that were documented on imaging, while five out of the six subjects had optic nerve abnormalities. Electrophysiologic testing was performed on three subjects, all of whom recorded abnormal results. An underlying neoplastic disorder was described for four subjects. Serum autoantibody testing results were available for four subjects. The serum testing included using antibodies against a 22-kDa antigen, a 35-kDa optic nerve-derived antigen, a 62-kDa antigen, enolase, recoverin, tubulin, and pyruvate kinase M2. Our subject presented 12 years after resection of a ganglioglioma with asymmetric bilateral vision loss, disc edema in one eye, advanced disc pallor in the fellow eye, and bilateral subtle retinal infiltrates, despite having a normal fluorescein angiogram. OCT demonstrated asymmetric ganglion cell layer thinning, which is consistent with the vision loss. Our subject also had abnormal brain MRI findings of widespread pachymeningeal enhancement, but he had a normal cerebrospinal fluid composition. He was initially treated with high-dose pulse steroids, followed by intravenous immunoglobulin therapy. He experienced partial visual recovery in both eyes. Conclusions Pediatric autoimmune retinopathy and optic neuropathy are rare diseases that can present with unique signs and symptoms. In pediatric patients who present with symptoms of subacute progressive vision loss with negative inflammatory workups, a history of prior neoplasm, and/or clinical findings of progressive retinopathy or optic neuropathy, an autoimmune process should be considered in the differential.